1977
DOI: 10.1021/jm00217a014
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazole anthelmintics

Abstract: A series of 3-halo-5-phenyl- and 3-phenyl-5-haloisoxazoles has demonstrated anthelmintic activity at doses ranging from 16 to 500 mg/kg orally against the rat roundworm, Nippostrongylus braziliensis. In the 5-phenyl series a halogen at the 3 position of the isoxazole ring was required for activity. However, in the 3-phenyl series activity was maintained after replacement of the 5-halogen with certain alkoxyl, thioalkoxyl, or amino groups. The 3-phenyl and 5-phenyl series apparently are not acting biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…The use of the unsymmetrical β-dicarbonyl compounds in the cyclocondensation reaction can lead to two possible isomers, and thus, the development of regioselective methods for the synthesis of heterocycle compounds became an important research area. In addition, the regioisomers 3-and 5-substitutedisoxazoles have shown different pharmacological activities in rodent parasite screen demonstrating still that these compounds possibly not acting at a common receptor site [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the unsymmetrical β-dicarbonyl compounds in the cyclocondensation reaction can lead to two possible isomers, and thus, the development of regioselective methods for the synthesis of heterocycle compounds became an important research area. In addition, the regioisomers 3-and 5-substitutedisoxazoles have shown different pharmacological activities in rodent parasite screen demonstrating still that these compounds possibly not acting at a common receptor site [8].…”
Section: Introductionmentioning
confidence: 99%
“…Analogs of 1 Several compounds, which have various substitution patterns of methoxyl groups on the phenyl moiety, are used clinically as vasodilators; these include dilazep (2), verapamil (3) and buflomedil (4). Therefore, the number and the locations of methoxyl groups of 1 were varied in order to clarify the role of the substituents.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Singh et al [5] synthesized the cobalt(II) complexes with somea cylhydrazones, which showed afair antifungal and antibacterial activity against anumber of fungi and bacteria. Otherwise, photoluminescence, photoabsorption and photoemission studies of hydrazone thin filmsused as hole transporting material in organic light emitting diodes (OLEDs) were reported [6].Onthe other hand, isoxazole compounds have arich history with both pharmaceutical and agricultural applications due to their apoptotic activity [7], plantgrowth regulating activity [8] and antibacterial activity [9]. In the title compound, C 12 H 11 N 3 O 3 ,the molecule is almost planar, the dihedral angle formed by the benzene and isoxazole rings is 2.03 (8) …”
Section: Discussionmentioning
confidence: 99%